Taxonomic revision of Calamister Kirkaldy, 1906 (Fulgoromorpha: Cixiidae) with the description of a new species - Löcker, Birgit (Zootaxa, 2014)
Calamister obscurus Kirkaldy, 1906 is redescribed, illustrated and a lectotype designated from the type series. A new species, C. cougalensis, is added to the genus. An identification key is provided and morphological characters discussed. Doubts are raised about a specimen published as C. obscurus by Jacobi (1928).